Anti-reflection atomization film layer and preparation method thereof, anti-reflection atomization coated glass and photovoltaic module

By applying a transmissive atomized film layer on the coated glass of the photovoltaic module, using a multi-stage pore structure and a micron-scale pit structure, the problems of blue unevenness and light transmittance of the photovoltaic module are solved, and the color consistency and Improved power generation efficiency.

CN119486376APending Publication Date: 2025-02-18SSI NEW MATERIAL (ZHENJIANG) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411516486.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-12
Filing Date
2024-10-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing photovoltaic modules have no main gate structure on the front of the back contact battery technology, which seriously affects the aesthetic appearance of the module. The existing impermeable coating technology will reduce the light transmittance while increasing the light transmittance of the glass. , affects power generation efficiency.

Method used

Adopt the atomized film layer, which is built into a multi-stage pore structure and a micro-scale pit structure on the surface. The refractive index of the film layer is reduced through the multi-stage pore structure, and the light transmittance is improved. The pit structure increases haze and covers Color difference of internal battery cells.

Benefits of technology

The color distribution of photovoltaic modules is achieved, the power generation power is improved, and high light transmittance and excellent dirt resistance and weather resistance are maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119486376A_ABST
    Figure CN119486376A_ABST
Patent Text Reader

Abstract

The invention provides an anti-reflection atomization film layer and a preparation method thereof, anti-reflection atomization coated glass and a photovoltaic module, a multi-stage pore structure is distributed in the anti-reflection atomization film layer, the multi-stage pore structure comprises a first pore and a second pore, and the pore diameter of the second pore is larger than that of the first pore; at least part of the second holes are flat holes, and pit structures are irregularly distributed on the surface of the film layer. The anti-reflection atomization film layer provided by the invention is colorless, the surface of photovoltaic glass is covered with the anti-reflection atomization film layer, and a battery piece in a photovoltaic module can be covered through the scattering effect of the film layer on light rays, so that the color distribution consistency of the photovoltaic module can be greatly improved; through the anti-reflection effect of the film layer on incident light, the anti-reflection effect is realized, and the power generation power of the photovoltaic module is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an anti-reflection atomized film layer and a preparation method thereof, anti-reflection atomized coated glass and a photovoltaic module, belonging to the technical field of photovoltaics. Background Art

[0002] At present, the solar photovoltaic industry has ushered in unprecedented development opportunities and challenges. Continuously improving the utilization rate of solar energy and reducing the cost of photovoltaic power generation has always been the development goal of photovoltaic industrialization. Among them, cell technology is one of the core technologies of photovoltaic modules. As the conversion efficiency of PERC cells (Passivated Emitter and Rear Cell) gradually approaches the theoretical limit, the iteration of cell technology has become an important breakthrough point in the industry. Among them, BC (Back Contact) technology, that is, back contact cell technology, has attracted major battery companies to put into production with its high energy density, long life, strong compatibility and environmental friendliness. It is estimated that the industry's production capacity will be nearly 60GW in 2023, and the market share will account for 15% in 2025, with an average annual expansion scale of about 40GW. The biggest feature and advantage of BC components is that all grid lines are placed on the back, realizing a main grid-free structure on the front, which increases the absorption of incident light by the cells and improves the photoelectric conversion efficiency, while also making the color distribution of the components more consistent, which can be perfectly integrated with the building.

[0003] As BC technology is widely used in high-end distributed components, people's requirements for components are not only about power generation efficiency, but also whether the color distribution tends to be consistent. However, one disadvantage of the special structure of BC cells without a main grid on the front is that the blue color of the cell itself is uneven (such as Figure 1 The BC module has uneven appearance color, which is mainly caused by two aspects. First, the coating layer of the existing photovoltaic glass has large color difference and presents uneven blue; second, the battery cells inside the module will also present uneven blue due to the uneven coating. At present, the mainstream solvent-based single-plating anti-reflection coating liquid in the market can neither improve the color difference problem itself nor cover the color difference of the battery cells inside the module. The double-plating colorless coating technology can improve the color difference problem of the film layer itself, but it is difficult to cover the color difference of the internal battery cells. For anti-glare coated glass, the haze is increased by adding large particles (micrometers or tens of micrometers) or increasing the thickness of the film layer (micrometers or tens of micrometers) in the film layer (for example, patent CN 115594875A), but the film layer on the anti-glare coated glass will greatly reduce the light transmittance of the glass, and even appear obvious whitening, which will have a serious impact on the power generation of photovoltaic modules.

[0004] Therefore, providing a new type of anti-reflection fogging film layer and its preparation method, anti-reflection fogging coated glass and photovoltaic module has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] In order to solve the above shortcomings and deficiencies, the purpose of the present invention is to provide an anti-reflection fogging film layer and a preparation method thereof, an anti-reflection fogging coated glass and a photovoltaic module. The anti-reflection fogging film layer provided by the present invention can not only improve the color difference of photovoltaic glass and improve the color distribution consistency of photovoltaic modules, but also cover the internal cells of the photovoltaic module.

[0006] In order to achieve the above objectives, on the one hand, the present invention provides an anti-reflection atomized film layer, wherein a multi-level pore structure is distributed inside the anti-reflection atomized film layer, the multi-level pore structure includes a first hole and a second hole, and the pore size of the second hole is larger than the first hole; the second hole is at least partially a flat hole, and the surface of the film layer is irregularly distributed with a pit structure.

[0007] The pit structure on the surface of the anti-reflection atomized film layer provided by the present invention can scatter light and achieve the atomization effect, while the internal multi-level hole structure mainly functions to enhance transmittance. At the same time, the second hole can also scatter light to a certain extent, thereby enabling the anti-reflection atomized film layer to achieve the atomization effect as a whole.

[0008] As a specific implementation of the above-mentioned anti-reflection atomized film layer of the present invention, the sizes of the pit structures are different, that is, the sizes are non-uniform.

[0009] As a specific embodiment of the above-mentioned anti-reflection atomized film layer of the present invention, the first holes and the second holes are both hollow closed-cell structures and are not connected to each other.

[0010] As a specific embodiment of the above-mentioned anti-reflection atomized film layer of the present invention, the pore size of the first pores ranges from 10 to 200 nm, preferably from 20 to 200 nm.

[0011] As a specific embodiment of the above-mentioned anti-reflection atomized film layer of the present invention, the pore size of the second pores ranges from 300 to 1000 nm, preferably from 400 to 900 nm, and more preferably from 450 to 800 nm.

[0012] The multi-level pore structure and the pit structure in the above-mentioned anti-reflection atomized film layer are both formed by inorganic nano-silicon dioxide particles.

[0013] As a specific embodiment of the above-mentioned anti-reflection atomized film layer of the present invention, the shape of the pit structure includes one or a combination of circular, elliptical and irregular shapes.

[0014] The surface of the anti-reflection atomized film layer provided by the present invention is relatively flat in some areas, and irregularly distributed with pit structures in some areas.

[0015] As a specific embodiment of the above anti-reflection atomized film layer of the present invention, the diameter of the pit structure ranges from 300-2000nm, preferably 600-1500nm, more preferably 800-1200nm. In the present invention, the diameter of the pit structure refers to the diameter of the plane circle where the edge of the pit structure is located.

[0016] As a specific implementation of the above-mentioned anti-reflection atomized film layer of the present invention, the average thickness of the anti-reflection atomized film layer is 50-1000 nm.

[0017] As a specific embodiment of the above anti-reflection haze film layer of the present invention, the light transmittance gain of the anti-reflection haze film layer is 0.2-1.5%, and the haze gain is ≥ 1.0. The test method of light transmittance gain and haze gain can be found in the following test example 1.

[0018] The present invention reduces the refractive index of the film layer and improves the light transmittance within the film layer thickness range of less than 1 μm by constructing a multi-level pore structure inside the film layer, and at the same time forms a special micron-level pit structure on the surface of the film layer to increase the haze, thereby achieving the effect of covering the color difference of the internal battery cell.

[0019] On the other hand, the present invention also provides a method for preparing the above-mentioned anti-reflection atomized film layer, wherein the preparation method comprises:

[0020] Step (1): mixing a silicon source, an acidic catalyst and a solvent and reacting them to obtain a silica sol; adding a polymer pore-forming agent to the silica sol, and then adding an auxiliary agent and mixing them evenly to obtain an anti-reflection atomized coating solution;

[0021] Step (2): coating the anti-reflection atomized coating liquid on the surface of a glass substrate, and calcining after surface drying to obtain the anti-reflection atomized film layer.

[0022] As a specific embodiment of the preparation method described above, in step (1), based on the total weight of the raw materials used to prepare the anti-reflection atomized coating solution being 100%, the polymer pore-forming agent in the raw materials accounts for 1-10%.

[0023] As a specific embodiment of the preparation method described above, in step (1), the raw materials include 2-6% silicon source, 0.1-1% acid catalyst, 1-10% polymer pore-forming agent, 0.1-2% auxiliary agent and the rest solvent, and the sum of the weight percentages of the components is 100%. For example, in some embodiments of the present invention, the amount of the solvent is 81-96.8%.

[0024] As a specific embodiment of the preparation method described above, in step (1), the anti-reflection atomized coating solution contains nanoparticles formed by a polymer pore-forming agent, and the size of the nanoparticles is 10-2000 nm.

[0025] As a specific embodiment of the preparation method described above of the present invention, in step (1), the silicon source includes one or two of alkoxysilane and tetraethyl orthosilicate, the acidic catalyst includes one or a combination of organic acid and inorganic acid, the solvent includes one or a combination of water, ethanol, isopropanol, and the auxiliary agent includes a surfactant and / or a wetting agent. In some embodiments of the present invention, the alkoxysilane may be, for example, tetramethoxysilane and / or tetraethoxysilane, the acidic catalyst may be selected from one or a combination of hydrochloric acid, phosphoric acid, acetic acid, citric acid, etc., and the wetting agent may be a wetting agent such as silicone, polyether, etc.

[0026] As a specific embodiment of the above preparation method of the present invention, in step (1), the polymer pore-forming agent includes one or both of polyurethane and polyacrylic acid.

[0027] As a specific embodiment of the preparation method described above, in step (1), the silicon source is hydrolyzed under acidic conditions to obtain nano-silicon dioxide particles, and the average particle size of the nano-silicon dioxide particles in the silica sol is 5-100 nm.

[0028] As a specific embodiment of the preparation method described above, in step (1), a silicon source and an acidic catalyst are added to a solvent and stirred at room temperature for 1-3 hours, and a polymer pore-forming agent is added to the silica sol and stirred.

[0029] As a specific embodiment of the preparation method described above of the present invention, in step (2), the coating method includes spin coating, roller coating, spray coating or pull-up dipping, etc.

[0030] As a specific embodiment of the preparation method described above, in step (2), after surface drying, curing can be carried out at room temperature or under heating conditions.

[0031] As a specific embodiment of the preparation method described above, in step (2), the calcination is carried out at 500-750° C. for 0.5-3 min. The calcination can be carried out in a radiation heating furnace.

[0032] In the present invention, the nanoparticles with a size of 10-2000nm formed by the polymer pore-forming agent in the anti-reflection atomized coating liquid form a hollow closed-pore structure inside the film layer and a pit structure on the surface after solvent volatilization, film formation and high-temperature calcination after coating. The multi-level pore structure inside the film layer includes uniformly distributed, small-sized second holes and larger-sized flat first holes, which can reduce the refractive index of the film layer and increase the transmittance of the light. In addition, the large-sized pit structure is distributed on the surface of the film layer, making the surface uneven and the roughness significantly increased, and finally achieving the atomization effect.

[0033] In summary, the present invention forms two special structures inside and on the surface of the film layer. Under the synergistic effect of the structures, the film layer can achieve both anti-reflection and atomization effects, thereby meeting the dual requirements of high efficiency and aesthetics of photovoltaic modules.

[0034] In yet another aspect, the present invention further provides an anti-reflection fogged coated glass, wherein the surface of the anti-reflection fogged coated glass is covered with the anti-reflection fogged film layer described above.

[0035] In yet another aspect, the present invention further provides a photovoltaic module, wherein the photovoltaic module comprises the anti-reflection fogged coated glass described above.

[0036] On the one hand, the anti-reflection atomized film provided by the present invention is colorless in itself, and on the other hand, it can improve the haze of the film while maintaining the transmittance to cover the color difference of the internal battery cells, so that the photovoltaic module as a whole presents a more uniform color. The successful application of this film in photovoltaic modules, such as BC modules, will greatly help the application of photovoltaic modules in the mid-to-high-end distributed household and industrial and commercial markets with high requirements for color distribution consistency and low price sensitivity.

[0037] Compared with the prior art, the beneficial technical effects that can be achieved by the present invention include:

[0038] The interior of the anti-reflection atomized film provided by the present invention has a rich multi-scale and multi-level pore structure, among which nanopores with a pore size of less than 200nm can effectively reduce the refractive index of the film layer and enhance the transmittance of light, and micro-nanopores with a pore size of more than 200nm can effectively enhance the scattering effect of the film layer on light, thereby increasing the atomization degree of the film layer and reducing the glossiness, which is an important factor in the film layer covering the color difference of the battery cell.

[0039] The surface of the anti-reflection atomized film layer provided by the present invention is a closed structure, so that it has excellent dirt resistance and weather resistance. At the same time, the special micron-level pit structure formed on the surface of the film layer can increase the haze, thereby achieving the effect of covering the color difference of the internal battery cells.

[0040] The anti-reflection atomized film layer provided by the present invention is colorless in itself. When it is covered on the surface of the photovoltaic glass, the light scattering effect of the film layer can cover the internal cells of the photovoltaic module, thereby greatly improving the color distribution consistency of the photovoltaic module; the anti-reflection effect of the film layer on the incident light can achieve an anti-reflection effect and improve the power generation capacity of the photovoltaic module. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 A schematic diagram of the overall color presentation of existing uncoated packaging components.

[0043] Figure 2a A schematic cross-sectional view of the anti-reflection fogged coated glass provided in an embodiment of the present invention.

[0044] Figure 2b A schematic diagram of the surface of the anti-reflection fogged coated glass provided in an embodiment of the present invention.

[0045] Figure 3a This is a scanning electron microscope image of the anti-reflection haze film layer in the anti-reflection haze coated glass provided in Example 1 of the present invention.

[0046] Figure 3b for Figure 3a An enlarged schematic diagram of .

[0047] Figure 4a This is a scanning electron microscope image of the surface of the coating layer in the conventional coated glass provided in Comparative Example 1.

[0048] Figure 4b This is a scanning electron microscope image of a 45° cross section of the coating layer in the conventional coated glass provided in Comparative Example 1.

[0049] Figure 5 This is a schematic diagram of the overall color presentation of a conventional film-coated packaging component.

[0050] Figure 6 This is a schematic diagram of the colors presented by the entire BC assembly assembled from the anti-reflection fogged coated glass provided in Example 1 in Test Example 1 of the present invention.

[0051] Description of main figures:

[0052] 1. Glass substrate;

[0053] 2. Anti-reflection atomization film layer. DETAILED DESCRIPTION

[0054] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0055] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​listed are 1 and 2, and the maximum range values ​​listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0056] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.

[0057] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.

[0058] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.

[0059] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0060] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the attached table, drawings and examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0061] Example 1

[0062] This embodiment provides an anti-reflection fogged coated glass, which is prepared by a preparation method comprising the following specific steps:

[0063] Step (1): 3 parts by weight of tetraethyl orthosilicate and 0.2 parts by weight of hydrochloric acid are weighed, added to 50 parts by weight of water, and stirred at room temperature for 2 hours to obtain a silica sol, wherein the average particle size of the nano-silica particles in the silica sol is 40 nm; 6 parts by weight of a polymer pore-forming agent (polyurethane) is added to the silica sol, and the mixture is stirred for 1 hour, followed by adding 0.2 parts by weight of an organic silicon wetting agent, and water is added to a total amount of 100 parts by weight, and the mixture is stirred for 30 minutes to obtain an anti-reflection atomized coating solution; the anti-reflection atomized coating solution contains nano-particles formed by the polymer pore-forming agent, and the size of the nano-particles is 10-2000 nm;

[0064] Step (2): coating is performed on a pre-cleaned and dried glass substrate with a thickness of 2.0 mm by roller coating, wherein the glass substrate is commercially available ultra-white embossed glass with a thickness of 2.0 mm and a light transmittance of 91.9%. After the surface is dried, the film layer is surface cured at a temperature of 150° C., and then calcined in a radiation heating furnace at a temperature of 720° C. for 1.5 minutes to be tempered, and then cooled to obtain the anti-reflection fogged coated glass.

[0065] The cross-sectional schematic diagram of the anti-reflection hazed coated glass provided in this embodiment is as follows Figure 2a Its surface schematic diagram is shown as Figure 2b As shown, the scanning electron microscope image of the anti-reflection fogging film layer in the anti-reflection fogging coated glass is as follows Figure 3a and Figure 3bAs shown. It can be seen from the figure that the anti-reflection fogged coated glass provided in this embodiment includes a glass substrate 1 and an anti-reflection fogged film layer 2 covering the surface of the glass substrate 1, and a multi-level pore structure is distributed inside the film layer, and the multi-level pore structure includes a first hole and a second hole, the pore size range of the first hole is between 10-200nm, and the average pore size of the first hole is 150nm; the pore size range of the second hole is between 300-1000nm, and the second hole includes some flat holes, and the average pore size of the second hole is 500nm. The surface of the anti-reflection fogged film layer 2 is irregularly distributed with pit structures, and the size of the pit structures is uneven, with a diameter range of 300-2000nm and an average diameter of 500nm. The average thickness of the anti-reflection fogged film layer is 100-500nm.

[0066] Example 2

[0067] This embodiment provides an anti-reflection fogged coated glass, which is prepared by a preparation method comprising the following specific steps:

[0068] Step (1): 3 parts by weight of tetraethyl orthosilicate and 0.3 parts by weight of phosphoric acid are weighed, added to 50 parts by weight of water, and stirred at room temperature for 1.5 hours to obtain a silica sol, wherein the average particle size of the nano-silica particles in the silica sol is 15 nm; 8 parts by weight of a polymer pore-forming agent (polyacrylic acid) is added to the silica sol, and the mixture is stirred for 2 hours, followed by adding 0.4 parts by weight of an organosilicon wetting agent, and water is added to a total amount of 100 parts by weight, and the mixture is stirred for 30 minutes to obtain an anti-reflection atomized coating solution; the anti-reflection atomized coating solution contains nano-particles formed by the polymer pore-forming agent, and the size of the nano-particles is 10-1600 nm;

[0069] Step (2): coating is performed on a pre-cleaned and dried glass substrate with a thickness of 2.0 mm by roller coating, wherein the glass substrate is the same as that used in Example 1. After the surface is dried, the film layer surface is cured at a temperature of 150° C., and then calcined in a radiation heating furnace at a temperature of 720° C. for 1.5 minutes for tempering, and then cooled to obtain the anti-reflection fogged coated glass.

[0070] The anti-reflection fogged coated glass provided in this embodiment includes a glass substrate and an anti-reflection fogged film layer covering the surface of the glass substrate, wherein a multi-level pore structure is distributed inside the film layer, and the multi-level pore structure includes a first hole and a second hole, wherein the aperture range of the first hole is between 10-100nm, and the average aperture of the first hole is 83nm; the aperture range of the second hole is between 500-1000nm, and the average aperture of the second hole is 650nm, and the second hole includes some flat holes. The surface of the anti-reflection fogged film layer is irregularly distributed with pit structures, and the pit structures are uneven in size, and the diameter range is 400-1600nm. The average thickness of the anti-reflection fogged film layer is 50-300nm.

[0071] Example 3

[0072] This embodiment provides an anti-reflection fogged coated glass, which is prepared by a preparation method comprising the following specific steps:

[0073] Step (1): Weigh 5 parts by weight of tetraethyl orthosilicate and 1 part by weight of citric acid, add them to a mixed solvent of 30 parts by weight of water and 30 parts by weight of ethanol, and stir at room temperature for 2.5 hours to obtain a silica sol, wherein the average particle size of the nano-silica particles in the silica sol is about 20 nm; add 5 parts by weight of a polymer pore-forming agent (polyurethane) to the silica sol, continue stirring for 1 hour, then add 0.1 parts by weight of an organosilicon wetting agent, add water to a total amount of 100 parts by weight, and continue stirring for 30 minutes to obtain an anti-reflection atomized coating solution; the anti-reflection atomized coating solution contains nanoparticles formed by the polymer pore-forming agent, and the size of the nanoparticles is 50-600 nm;

[0074] Step (2): coating is performed on a pre-cleaned and dried glass substrate with a thickness of 2.0 mm by roller coating, wherein the glass substrate is the same as that used in Example 1. After the surface is dried, the film layer surface is cured at a temperature of 150° C., and then calcined in a radiation heating furnace at a temperature of 720° C. for 1.5 minutes for tempering, and then cooled to obtain the anti-reflection fogged coated glass.

[0075] The anti-reflection fogged coated glass provided in this embodiment includes a glass substrate and an anti-reflection fogged film layer covering the surface of the glass substrate, wherein a multi-level pore structure is distributed inside the film layer, and the multi-level pore structure includes a first hole and a second hole, wherein the aperture range of the first hole is between 50-200nm, and the average aperture of the first hole is 173nm; the aperture range of the second hole is between 300-600nm, and the average aperture of the second hole is 415nm, and the second hole includes some flat holes. The surface of the anti-reflection fogged film layer is irregularly distributed with pit structures, and the pit structures are uneven in size, and the diameter range is 350-500nm. The average thickness of the anti-reflection fogged film layer is 200-1000nm.

[0076] Comparative Example 1

[0077] This comparative example provides a coated glass, which is prepared by a preparation method comprising the following specific steps:

[0078] Step (1): purchasing the commercially available E2 single-layer anti-reflection coating liquid produced by Shanghai Xiyuan New Energy Technology Co., Ltd.;

[0079] Step (2): coating is performed on a pre-cleaned and dried glass substrate with a thickness of 2.0 mm by roller coating, wherein the glass substrate is the same as that used in Example 1. After the surface is dried, the film layer surface is cured at a temperature of 150° C., and then calcined in a radiation heating furnace at a temperature of 720° C. for 1.5 minutes to be tempered, and then cooled to obtain the coated glass.

[0080] The scanning electron microscope images of the coating layer surface and the scanning electron microscope images of the 45° cross section of the coating layer in the conventional coated glass provided in Comparative Example 1 are shown as follows: Figure 4a and Figure 4b As shown. Figure 3a-Figure 3b and Figure 4a-4b It can be seen that, compared with the anti-reflection haze film layer in the anti-reflection haze coated glass provided in Example 1 of the present invention, the coating layer in the conventional coated glass provided in Comparative Example 1 has no multi-level pore structure inside and a smooth surface without a pit structure. Among them, the size of the internal pore structure of the film layer of Comparative Example 1 is basically the same, with an average diameter of 50nm.

[0081] Comparative Example 2

[0082] This comparative example provides an atomized coated glass, which is prepared by a preparation method comprising the following steps:

[0083] Step (1): 3 parts by weight of tetraethyl orthosilicate and 0.2 parts by weight of hydrochloric acid are weighed, added to 50 parts by weight of water, and stirred at room temperature for 2 hours to obtain a silica sol, wherein the average particle size of the nano-silica particles in the silica sol is 40 nm; 12 parts by weight of a polymer pore-forming agent (polyurethane) is added to the silica sol, and the stirring is continued for 1 hour, followed by adding 0.2 parts by weight of an organic silicon wetting agent, and water is added to a total amount of 100 parts by weight, and the stirring is continued for 30 minutes to obtain a coating solution; the anti-reflection atomized coating solution contains nanoparticles formed by the polymer pore-forming agent, and the size of the nanoparticles is 10-800 nm;

[0084] Step (2): coating is performed on a pre-cleaned and dried glass substrate with a thickness of 2.0 mm by roller coating, wherein the glass substrate is the same as that used in Example 1. After the surface is dried, the film layer surface is cured at a temperature of 150° C., and then calcined in a radiation heating furnace at a temperature of 720° C. for 1.5 minutes to be tempered, and then cooled to obtain the atomized coated glass.

[0085] The atomized coated glass provided in this comparative example includes a glass substrate and an atomized film layer covering the surface of the glass substrate, wherein a multi-level pore structure is distributed inside the film layer, and the multi-level pore structure includes a first hole and a second hole, wherein the aperture range of the first hole is between 10-50nm, and the average aperture of the first hole is 43nm; the aperture range of the second hole is between 300-500nm, and the average aperture of the second hole is 347nm, and the second hole includes some flat holes. The surface of the atomized film layer is irregularly distributed with pit structures, and the pit structures are uneven in size, and the diameter range is 300-800nm. The average thickness of the atomized film layer is 100-500nm.

[0086] Test Example 1

[0087] In this test example, the coated glass and blank glass (the same glass substrate as used in Example 1) provided in the embodiment and comparative example, BC cells, adhesive film and black organic backplane are respectively packaged into BC modules, and then the BC modules are placed vertically in the sun, and the appearance of the BC modules is observed from a distance of 2 meters to test the effect of the coated glass in covering the color difference of the cells. The uniform color is qualified. In this test example, the light transmittance and haze of the coated glass provided in the embodiment and comparative example are also measured respectively.

[0088] The transmittance test includes the following specific steps: using Abotek transmittance tester to measure the transmittance of blank glass and coated glass in the 380-1100nm band respectively, each sample is tested at least three times, the average value is taken and used as the transmittance of blank glass and coated glass, and then the difference between the transmittance of coated glass and blank glass is calculated and used as the transmittance gain.

[0089] The haze test includes the following steps: using a haze meter to measure the haze values ​​of blank glass and coated glass in the 400-780nm band respectively, each sample is tested at least three times, the average value is taken and used as the haze value of the blank glass and coated glass, and then the difference between the haze of the coated glass and the haze of the blank glass is calculated and used as the haze gain.

[0090] In this test example, the experimental results of effective transmittance, that is, transmittance, haze and cell color covering effect are shown in Table 1 below.

[0091] Table 1

[0092]

[0093]

[0094] It can be seen from Table 1 above that the transmittance gain of the anti-reflection hazed coated glass provided by Examples 1 to 3 of the present invention is adjustable in the range of 0.2-1.5%, and the haze gain is ≥1.0, preferably ≥2.0; since an excessive amount of polymer pore-forming agent is used in Comparative Example 2, the surface of the anti-reflection hazed film layer in the prepared coated glass has more pit structures and more scattering, so that its transmittance (effective transmittance and transmittance gain) is significantly lower, which is significantly lower than the anti-reflection hazed coated glass provided by Examples 1 to 3 of the present invention;

[0095] Compared with blank glass, the anti-reflection hazed coated glasses provided in Examples 1 to 3 of the present invention all have higher effective transmittance and haze, and can better enhance transmittance and conceal the chromatic aberration of the cell, and the effect of concealing the chromatic aberration of the cell is significant;

[0096] Although the size of a single pore of the coated glass provided in Comparative Example 1 is not large, the number of pores is large and the distribution is uniform, so the light transmittance gain is high and the light transmission performance is high. However, since the surface of the coating layer of the coated glass provided in Comparative Example 1 is smooth and has no pit structure, the haze gain is low and cannot achieve covering.

[0097] In this test example, the color diagram of the BC assembly assembled by the anti-reflection fogged coated glass provided in Example 1 is as follows: Figure 6 As shown, the color schematic diagram of the conventional coating packaging component provided in Comparative Example 1 is as follows Figure 5 shown.

[0098] Compare with the above Figure 5 and Figure 6 It can be seen that the anti-reflection atomized film layer provided in Example 1 of the present invention is colorless in itself. When it is covered on the surface of the photovoltaic glass, the film layer can cover the internal cells of the photovoltaic module through the scattering effect of the light, thereby greatly improving the color distribution consistency of the photovoltaic module; the anti-reflection effect of the film layer on the incident light can achieve the anti-reflection effect and improve the power generation power of the photovoltaic module. Figure 5 As shown, the existing coating solution cannot cover the color difference.

[0099] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.

Claims

1. An anti-reflection atomized film layer, characterized in that: The anti-reflection atomizing film layer has a multi-level pore structure distributed inside, the multi-level pore structure includes a first hole and a second hole, and the aperture of the second hole is larger than the first hole; the second hole is at least partially a flat hole, and the surface of the film layer has irregularly distributed pit structures.

2. The anti-reflection atomized film layer according to claim 1, characterized in that: The first hole and the second hole are both hollow closed-cell structures.

3. The anti-reflection atomized film layer according to claim 1 or 2, characterized in that: The pore size of the first pore ranges from 10 to 200 nm.

4. The anti-reflection atomized film layer according to claim 1 or 2, characterized in that: The pore size of the second pores ranges from 300 to 1000 nm, preferably from 400 to 900 nm, and more preferably from 450 to 800 nm.

5. The anti-reflection atomized film layer according to claim 1, characterized in that: The shape of the pit structure includes one or a combination of circular, elliptical and irregular shapes.

6. The anti-reflection atomized film layer according to claim 1 or 5, characterized in that: The diameter of the pit structure ranges from 300 to 2000 nm, preferably from 600 to 1500 nm, and more preferably from 800 to 1200 nm.

7. The anti-reflection atomized film layer according to claim 1, characterized in that: The average thickness of the anti-reflection atomized film layer is 50-1000 nm, preferably 80-500 nm.

8. The anti-reflection atomized film layer according to any one of claims 1-2, 5, and 7, characterized in that: The transmittance gain of the anti-reflection haze film layer is 0.2-1.5%, and the haze gain is ≥1.

0.

9. The method for preparing the anti-reflection atomized film layer according to any one of claims 1 to 8, characterized in that: The preparation method comprises: Step (1): mixing a silicon source, an acidic catalyst and a solvent and reacting them to obtain a silica sol; adding a polymer pore-forming agent to the silica sol, and then adding an auxiliary agent and mixing them evenly to obtain an anti-reflection atomized coating solution; Step (2): coating the anti-reflection atomized coating liquid on the surface of a glass substrate, and calcining after surface drying to obtain the anti-reflection atomized film layer.

10. The preparation method according to claim 9, characterized in that: Taking the total weight of the raw materials used to prepare the anti-reflection atomized coating solution as 100%, the polymer pore-forming agent in the raw materials accounts for 1-10%; Preferably, based on the total weight of raw materials used to prepare the anti-reflection atomized coating solution as 100%, the raw materials include 2-6% silicon source, 0.1-1% acid catalyst, 1-10% polymer pore former, 0.1-2% auxiliary agent and the balance solvent.

11. The preparation method according to claim 9 or 10, characterized in that: The anti-reflection atomized coating solution contains nanoparticles formed by a polymer pore-forming agent, and the size of the nanoparticles is 10-2000nm.

12. The preparation method according to claim 9 or 10, characterized in that: The silicon source includes one or two of alkoxysilane and tetraethyl orthosilicate, the acid catalyst includes one or a combination of organic acid and inorganic acid, the solvent includes one or a combination of water, ethanol and isopropanol, and the auxiliary agent includes a surfactant and / or a wetting agent.

13. The preparation method according to claim 9 or 10, characterized in that: The polymer pore-forming agent includes one or both of polyurethane and polyacrylic acid.

14. The preparation method according to claim 9 or 10, characterized in that: The average particle size of the nano-silica particles in the silica sol is 5-100 nm. 15.An anti-reflection fogged coated glass, characterized in that: The surface of the anti-reflection fogged coated glass is covered with the anti-reflection fogged film layer according to any one of claims 1 to 8.

16. A photovoltaic module, characterized in that: The photovoltaic module includes the anti-reflection fogged coated glass as described in claim 15.

Citation Information

Cited By

  • Anti-reflective hazing film layer and preparation method therefor, Anti-reflective hazing coated glass, and photovoltaic module

    WO2025256413A1